Analisis Kontur Isodosis Radiasi Sinar-X di Instalasi Radiologi Rumah Sakit Umum Daerah Labuang Baji Makassar - Normawati, Sitti; Jumardin, Jumardin; Ulandari, Resky; Dg Manarang, Hidayat (JFT: Jurnal Fisika dan Terapannya, 2025)
Isodosis contour analysis using surfer type 21 software has been conducted in the radiology installation of Labuang Baji Hospital Makassar to determine the safest distance for radiology medical personnel while in the X-ray aircraft area. Measurements were carried out before and during exposure to a water phantom using an X-ray aircraft with a surveymeter. Radiation exposure rates were measured at 8 track locations in the X-ray aircraft room, consisting of 16 points located on the track (A, B, C, D, E, F, G, H) at 1 m and 1.5 m heights. The processed data showed that the highest radiation exposure dose was in the E-1 track (in front of the X-ray plane), which was 0.001791 mSv with a radiation dose exposure rate of 43.320 mSv/hour for a height of 1 m and 0.001228 mSv in the A-1 track for a height of 1.5 m with a radiation dose exposure rate of 29.7997 mSv/hour. The isodose contours also show variations in the number of passes and different colors for each radiation exposure dose value. The findings of this study indicate that the radiation exposure dose is 0 mSv at a distance of more than 2 m from the X-ray plane, so the radiologist is within safe limits to perform radiodiagnostic procedures.